Development of hydropower sustainability assessment method in Malaysia context - Nur Atiqah, Omar (2017)
Nowadays, Malaysian energy companies started to pay attention to hydropower projects as this hydropower is one of the electricity source in Malaysia. However, emergence of the hydropower will lead to environmental, society and economic issues. All of these issues if not handled comprehensively will become more serious and endanger our planet also society. To remain competitive to other industries in Malaysia such in manufacturing, automotive and other else, an implementation of sustainability is very important to growth their business performance. In addition, sustainability is vital to Bursa Malaysia Securities Berhad under their listing requirements. Therefore, this study aims to develop a sustainability assessment practice for hydropower sector in Malaysia context by referring to Hydropower Sustainability Assessment Protocol (HSAP) and Green Project Management (GPM) P5 concept. The sustainability practice adopted in hydropower project generally follow Environmental Impact Assessments (EIAs) concept which focused only on environmentally issues. Thus, this study is to improve Systematic Sustainability Assessment (SSA) by integrating original SSA with HSAP that related to the hydropower industry. As a result, a satisfactory from the state council or auditor to the project standard will be achieved. In addition, this study, will contribute a number of factors towards sustainability performance of hydropower sector in Malaysia including provide a sustainable integrated reporting toward the project and provide a new sustainability approach to project manager.